Using Environmental Physiology to Teach Physiological Regulation - Shawn R. Simonson (MDPI AG, 2021)
Environmental Physiology at Boise State University, Idaho, is a multidisciplinary course that expands students' understanding of human regulatory physiology through acute and chronic responses to environmental extremes. Students explore the physics (pressure, fluid dynamics, gas laws, sound, and light) of the underwater environment, marine flora and fauna adaptations to this environment, and the human experience within this environment. Included is completion of the Professional Association of Dive Instructors (PADI) Open Water Scuba Certification. The course culminates in an international dive trip where course concepts are further demonstrated and explored, and conservation activities are undertaken.